METHODS FOR INTERNALIZING THE VALUES OF FAITH AND PIETY FROM THE PERSPECTIVE OF THE JALALAIN TAFSIR IN ISLAMIC RELIGIOUS EDUCATION IN THE DIGITAL AGE - Nimatul Khoeriyah; Enjang Burhanudin Yusuf (LP2M IAI Al-Khairat Pamekasan, 2026)
Digital transformation has significantly shifted how learners access and internalize religious values, requiring innovative approaches to Islamic Religious Education (PAI). This study analyzes the concepts of īman and taqwa in Tafsir Jalalain and formulates a value internalization model contextualized for PAI learning in the digital era. Using qualitative library research supported by limited field observation, this study examines Jalalain’s interpretation of selected Qur’anic verses and synthesizes contemporary Islamic education literature. Findings indicate that Jalalain emphasizes faith in the unseen, discipline in worship, self-control, and moral habituation. These principles are adapted into a digital learning framework through multimedia-based tadabbur, Qur’anic admonition, digital role modeling, application-based worship habituation, and electronic self-reflection. The study proposes the “I-Taqwa Jalalain Model” as an integrative strategy for internalizing Islamic values through technology-enhanced learning. This model strengthens the pedagogic relevance of classical tafsir in shaping student religiosity within modern technological ecosystems.